2023
DOI: 10.1039/d2dt03665g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and a combined experimental/theoretical structural study of a comprehensive set of Pd/NHC complexes witho-,m-, andp-halogen-substituted aryl groups (X = F, Cl, Br, CF3)

Abstract: A complete series of free NHC ligands and Pd/NHC complexes with –F, –Cl, –Br, and –CF3 substituents at the o-, m-, and p-positions of the aryl ring were synthesized and characterized. An increase of catalytic activity was observed in the Mizoroki–Heck reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…(NHC F )PdCl 2 Py complexes were prepared using a previously described method, with a slight decrease in yield for complexes 3e , 3f and 3j (Table 1). 40,41 Complexes 3a–j are air- and moisture-stable compounds that are almost insoluble in water and nonpolar organic solvents. The synthesis of compound 3ja {1,3-bis[2,4,6-trifluorophenyl]-imidazol-2-ylidene}dichloro(pyridine) palladium, carried out under the same conditions as the other complexes, yielded the product 3jb (SP-4-1)-[[2,2′-(1 H -Imidazole-1,3(2 H )-diyl-κC 2 )bis[4,6-bisfluorophenolato-κO]](4-)](pyridine)palladium containing chelated O-groups in the o -position instead of fluorine atoms.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(NHC F )PdCl 2 Py complexes were prepared using a previously described method, with a slight decrease in yield for complexes 3e , 3f and 3j (Table 1). 40,41 Complexes 3a–j are air- and moisture-stable compounds that are almost insoluble in water and nonpolar organic solvents. The synthesis of compound 3ja {1,3-bis[2,4,6-trifluorophenyl]-imidazol-2-ylidene}dichloro(pyridine) palladium, carried out under the same conditions as the other complexes, yielded the product 3jb (SP-4-1)-[[2,2′-(1 H -Imidazole-1,3(2 H )-diyl-κC 2 )bis[4,6-bisfluorophenolato-κO]](4-)](pyridine)palladium containing chelated O-groups in the o -position instead of fluorine atoms.…”
Section: Resultsmentioning
confidence: 99%
“…This was observed in our previous studies, where we investigated the steric effect of a o -substituent on M/NHC complexes, and the dependence of σ- and π-bonds stabilization energy on the dihedral angle between the phenyl and imidazolium rings. 40,41,43 Huynh and coworkers have also previously discovered the importance of the dihedral angle in modulating the electronic properties of NHCs, especially with respect to their σ- and π-bonds. When the dihedral angle between the wingtip substituent and the carbene plane changes, it affects the energies of the HOMO and π-HOMO orbitals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In many instances of Mizoroki-Heck coupling reactions catalyzed by Pd NHC complexes, a high Pd loading, and more reactive and often costlier aryl bromides or iodides are typically needed as substrates. [36][37][38][39][40][41][42][43][44][45] Among our newly prepared complexes, the one containing an electron-donating trialkylphosphine moiety in the ligand system exhibited the most promising catalytic activity in the coupling of electrondeficient aryl chlorides with alkenes. Theoretical calculations revealed that the ligand system in this complex is the most electron-donating, forming the strongest Pd-C and Pd-N bonds compared to other complexes featuring alternative phosphine moieties.…”
Section: Introductionmentioning
confidence: 99%